A Study of the Effects of Knowledge Management on Enterprise Innovation Performance - Qu, Juanjuan; Batool, Hira; Ullah, Kalim (Emerging Science Journal, 2025)
This study aims to explore how knowledge management capability and enterprise innovation behavior jointly affect the innovation performance of manufacturing SMEs. Based on the background of the knowledge economy, we selected manufacturing SMEs with knowledge as their core competitiveness as the research object and constructed and optimized the theoretical model of “Knowledge Management Capability-Innovation Behavior-Innovation Performance”. Based on the research data from 400 manufacturing SMEs in China, the study adopts the empirical analysis method and examines the relationship between the variables through structural equation modeling. The results show that knowledge management capability has a significant positive impact on firms' innovation performance, while firms' innovation behavior mediates the relationship between knowledge management capability and innovation performance. The findings of this study not only validate the key role of knowledge management in enhancing the innovation capability of enterprises but also reveal the path mechanism for enterprises to realize knowledge transformation and innovation results by stimulating innovative behaviors. Compared with previous studies, this study systematically optimizes the construction of theoretical models and the analysis of mediating effects, enriches the research content in the field of knowledge management and innovation performance, and provides new theoretical support and empirical evidence for the knowledge management practice and innovation strategy formulation of manufacturing SMEs.